A novel mass spectrometry‐based method for determining insulin‐like growth factor 1: assessment in a cohort of subjects with newly diagnosed acromegaly. (25th January 2013) - Kay, Richard; Halsall, David J.; Annamalai, Anand K.; Kandasamy, Narayanan; Taylor, Kevin; Fenwick, Susanna; Webb, Alison; Wark, Gwen; Pleasance, Steve; Gurnell, Mark
Summary Objective To develop an alternative method to immunoassay for the quantitative analysis of insulin‐like growth factor 1 (IGF‐1) using a mass spectrometry (MS)‐based approach. Study design and patients A stable isotope dilution Ultra High Performance Liquid Chromatography tandem MS (uHPLC‐MS/MS)‐based method for the quantification of IGF‐1 was developed. The method employed Selected Reaction Monitoring (SRM) of two tryptic peptides derived from IGF‐1, and utilised solid phase extraction for enrichment of the peptide fraction containing IGF‐1 rather than immunocapture, so was less susceptible to assay interference. Plasma samples from 25 consecutive unselected patients with newly diagnosed acromegaly, collected both before and after 24 weeks of primary medical therapy with Lanreotide Autogel®, were analysed by a widely used commercial immunoassay (Siemens Immulite 2000®) and by uHPLC‐MS/MS. Results The uHPLC‐MS/MS method showed good correlation with the immunoassay over a wide range of IGF‐1 concentrations. The Passing and Bablock regression was: uHPLC‐MS/MS (nmol/l) = 1·37 (95% confidence interval: 1·26–1·46) × immunoassay (nmol/l) + 3·14 (95% confidence interval: –2·71 to 10·32). Six patients had discordant growth hormone (GH) and IGF‐1 levels following primary medical therapy, and in all six the immunoassay and uHPLC‐MS/MS platforms returned comparable results. The method was not affected by concentrations of IGFBP3 up to 12 500 ng/ml. Conclusions uHPLC‐MS/MS offers an independent method for determining/validating IGF‐1 in subjects with acromegaly. Further studies, including the establishment of age‐ and sex‐matched reference ranges and calibration to the new International IGF‐1 standard IS 02/254, are now required to allow its introduction in to routine clinical use.